2015
DOI: 10.18632/oncotarget.4833
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram anti-cancer efficacy without copper overload is enhanced by extracellular H2O2 generation: antagonism by tetrathiomolybdate

Abstract: Highlightsexogenous SOD increases apoptosis by sub-toxic disulfiram without copper overloadH2O2 generation from glucose oxidase also potentiates disulfiram toxicityN-acetylcysteine suppresses antitumor potentiation of DSF by H2O2 generationsub-toxic tetrathiomolybdate inhibits potentiation of DSF by SODBackgroundCu/Zn superoxide dismutases (SODs) like the extracellular SOD3 and cytoplasmic SOD1 regulate cell proliferation by generating hydrogen peroxide (H2O2). This pro-oxidant inactivates essential cysteine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 58 publications
(125 reference statements)
4
21
0
Order By: Relevance
“…It is further notable that sulfide can increase the activities of Mn-SOD and Cu/Zn-SOD, both by upregulating their gene expression and by direct interaction with Cu/Zn-SOD [49]. Conversely, ATTM has been identified as a SOD inhibitor, a mechanism believed partially responsible for its efficacy as an anti-cancer agent [50]. It hence appears contradictory that ATTM-treatment induced an increase in SOD (and catalase) activity after tMCAO.…”
Section: Discussionmentioning
confidence: 99%
“…It is further notable that sulfide can increase the activities of Mn-SOD and Cu/Zn-SOD, both by upregulating their gene expression and by direct interaction with Cu/Zn-SOD [49]. Conversely, ATTM has been identified as a SOD inhibitor, a mechanism believed partially responsible for its efficacy as an anti-cancer agent [50]. It hence appears contradictory that ATTM-treatment induced an increase in SOD (and catalase) activity after tMCAO.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the active metabolite of DSF when it is used in combination with copper is a dithiocarb-copper complex [17] , [34] . Because this complex can damage normal tissues, different ways to increase the DSF toxicity without the use of copper ions and to protect the adjacent tissues by encapsulating the components into micro- and nanoparticles are developed to date [15] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, its potential as an anticancer drug and as an adjuvant therapy has been tested both in preclinical studies and clinical trials [23, 2527]. The mechanisms of DSF's anticancer effects are versatile.…”
Section: Introductionmentioning
confidence: 99%